Acoustic wave device, filter, and multiplexer
By employing a lithium niobate and lithium tantalate layer configuration with specific cut angles and thickness ratios, the frequency-temperature characteristics of surface acoustic wave resonators are enhanced, addressing the inconsistency between resonant and anti-resonant frequencies.
Patent Information
- Application Number
- JP2023107005
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
Existing surface acoustic wave resonators face challenges in maintaining consistent frequency-temperature characteristics between the resonant and anti-resonant frequencies due to differing frequency temperature coefficients, making it difficult to improve both simultaneously.
The use of a piezoelectric layer comprising a lithium niobate layer and a lithium tantalate layer, with specific cut angles and thickness ratios, to create a configuration where the frequency temperature coefficients of both resonant and anti-resonant frequencies are aligned, reducing the difference between them.
This configuration effectively reduces the difference in frequency temperature coefficients, improving the overall frequency-temperature stability and performance of the acoustic wave device.
Smart Images

Figure 2025006298000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to acoustic wave devices, filters, and multiplexers. [Background technology]
[0002] Surface acoustic wave resonators are known as acoustic wave devices used in communication devices such as smartphones. A configuration is known in which a piezoelectric layer forming a surface acoustic wave resonator is attached to a substrate. It is known that the thickness of the piezoelectric layer provided on the substrate is set to be equal to or less than the wavelength of the acoustic wave in order to suppress spurious (for example, Patent Document 1). It is known that a temperature compensation layer made of a silicon oxide film is provided between the substrate and the piezoelectric layer in order to improve the frequency-temperature characteristic and suppress loss, and the total thickness of the temperature compensation layer and the piezoelectric layer is set to be equal to or less than twice the wavelength of the acoustic wave (for example, Patent Document 2). Also, a configuration is known in which an intermediate layer, which has a faster sound velocity of a transverse wave than the piezoelectric layer, is provided on the lower surface of the piezoelectric layer in order to improve the frequency-temperature characteristic and suppress loss, and a temperature compensation layer is provided on the lower surface of the intermediate layer (for example, Patent Document 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-34363 A [Patent Document 2] JP 2019-201345 A [Patent Document 3] JP 2020-123855 A Summary of the Invention [Problem to be solved by the invention]
[0004] In Patent Document 2 and Patent Document 3, a temperature compensation layer is provided between the substrate and the piezoelectric layer to improve the frequency temperature characteristic. However, in a surface acoustic wave resonator, the frequency temperature coefficient of the resonant frequency is different from the frequency temperature coefficient of the anti-resonant frequency. Therefore, a difference occurs between the frequency temperature coefficient of the resonant frequency and the frequency temperature coefficient of the anti-resonant frequency, and the inventions described in Patent Document 2 and Patent Document 3 can improve the frequency temperature coefficient of either the resonant frequency or the anti-resonant frequency, but it is difficult to improve the frequency temperature coefficients of both the resonant frequency and the anti-resonant frequency.
[0005] The present invention has been made in consideration of the above-mentioned problems, and has an object to reduce the difference between the frequency temperature coefficient of the resonant frequency and the frequency temperature coefficient of the anti-resonant frequency. [Means for solving the problem]
[0006] The present invention is an acoustic wave device comprising: a substrate; a piezoelectric layer provided on the substrate, the piezoelectric layer having a lithium niobate layer and a lithium tantalate layer provided between the substrate and the lithium niobate layer; and a pair of comb electrodes provided on the lithium niobate layer, each of the comb electrodes having a plurality of electrode fingers that excite acoustic waves, the average pitch of the plurality of electrode fingers of one comb electrode being equal to or greater than the distance from the upper surface of the lithium niobate layer to the lower surface of the lithium tantalate layer.
[0007] In the above configuration, the lithium niobate layer is a rotated Y-cut X-propagation lithium tantalate layer, and the lithium tantalate layer is a rotated Y-cut X-propagation lithium tantalate layer, and when a total thickness of the lithium niobate layer and the lithium tantalate layer is taken as 100%, when a cut angle of the lithium niobate layer is 0° or more and less than 55°, a thickness ratio of the lithium niobate layer is more than 0% and 36% or less, when a cut angle of the lithium niobate layer is 55° or more and less than 70°, a thickness ratio of the lithium niobate layer is more than 5% and 54% or less, and when a cut angle of the lithium niobate layer is 70° or more and 80° or less, a thickness ratio of the lithium niobate layer is more than 10% and 85% or less.
[0008] In the above configuration, the lithium niobate layer is a rotated Y-cut X-propagation lithium tantalate layer, and the lithium tantalate layer is a rotated Y-cut X-propagation lithium tantalate layer having a cut angle of 50° or less, and when the cut angle of the lithium niobate layer is 0° or more and less than 30°, the ratio of the thickness of the lithium niobate layer to the total thickness of the lithium niobate layer is more than 5% and 24% or less, when the cut angle of the lithium niobate layer is 30° or more and less than 50°, when the total thickness of the lithium niobate layer and the lithium tantalate layer is 100%. The thickness ratio of the lithium niobate layer can be greater than 10% and less than 27%, and when the cut angle of the lithium niobate layer is greater than 50° and less than 60°, the thickness ratio of the lithium niobate layer can be greater than 10% and less than 30%, and when the cut angle of the lithium niobate layer is greater than 60° and less than 70°, the thickness ratio of the lithium niobate layer can be greater than 15% and less than 34%, and when the cut angle of the lithium niobate layer is greater than 70° and less than 80°, the thickness ratio of the lithium niobate layer can be greater than 15% and less than 50%.
[0009] The present invention is an acoustic wave device comprising: a substrate; a piezoelectric layer provided on the substrate, the piezoelectric layer having a lithium tantalate layer and a lithium niobate layer provided between the substrate and the lithium tantalate layer, the thicknesses of the lithium tantalate layer and the lithium niobate layer both accounting for 10% or more of the total thickness of the lithium tantalate layer and the lithium niobate layer being 100%; and a pair of comb electrodes provided on the lithium tantalate layer, each of the comb electrodes having a plurality of electrode fingers that excite acoustic waves, the average pitch of the plurality of electrode fingers of one comb electrode being equal to or greater than the distance from the upper surface of the lithium tantalate layer to the lower surface of the lithium niobate layer.
[0010] In the above configuration, the lithium tantalate layer is a rotated Y-cut X-propagation lithium tantalate layer having a cut angle of 50° or less, and the lithium niobate layer is a rotated Y-cut X-propagation lithium niobate layer, and when the total thickness of the lithium tantalate layer and the lithium niobate layer is taken as 100%, when the cut angle of the lithium tantalate layer is 0° or more and less than 22.5°, the thickness ratio of the lithium tantalate layer is 10% or more and 40% or less, when the cut angle of the lithium tantalate layer is 22.5° or more and less than 37.5°, the thickness ratio of the lithium tantalate layer is 10% or more and 51% or less, and when the cut angle of the lithium tantalate layer is 37.5° or more and 50° or less, the thickness ratio of the lithium tantalate layer can be 13% or more and 85% or less.
[0011] In the above configuration, the lithium tantalate layer is a rotated Y-cut X-propagation lithium tantalate layer having a cut angle of 50° or less, and the lithium niobate layer is a rotated Y-cut X-propagation lithium niobate layer, and when the total thickness of the lithium tantalate layer and the lithium niobate layer is taken as 100%, when the cut angle of the lithium tantalate layer is 0° or more and less than 10°, the thickness ratio of the lithium tantalate layer is 12% or more and 20.5% or less, and when the cut angle of the lithium tantalate layer is 10° or more and less than 22.5°, the thickness ratio of the lithium tantalate layer is 12% or more and 26% or less, and When the cut angle of the lithium tantalate layer is 22.5° or more and less than 27.5°, the thickness ratio of the lithium tantalate layer is 12% or more and 34% or less, when the cut angle of the lithium tantalate layer is 27.5° or more and less than 35°, the thickness ratio of the lithium tantalate layer is 12% or more and 41% or less, when the cut angle of the lithium tantalate layer is 35° or more and less than 45°, the thickness ratio of the lithium tantalate layer is 21% or more and 46% or less, and when the cut angle of the lithium tantalate layer is 45° or more and less than 50°, the thickness ratio of the lithium tantalate layer can be 25.5% or more and 50% or less.
[0012] In the above structure, the lithium niobate layer and the lithium tantalate layer may be directly bonded to each other.
[0013] The present invention is an acoustic wave device comprising: a substrate; a first layer provided on the substrate and made of a piezoelectric material; and a second layer provided between the substrate and the first layer and made of a piezoelectric material, wherein when a pair of comb electrodes are provided on each of the first layer and the second layer, the frequency temperature coefficient of the resonant frequency in one of the first layer and the second layer is greater than the frequency temperature coefficient of the resonant frequency in the other layer and the frequency temperature coefficient of the anti-resonant frequency in the one layer is smaller than the frequency temperature coefficient of the anti-resonant frequency in the other layer, and when the total thickness of the first layer and the second layer is taken as 100%, the thicknesses of the first layer and the second layer both account for 10% or more; and a pair of comb electrodes provided on the first layer, each having a plurality of electrode fingers that excite acoustic waves, wherein the average pitch of the plurality of electrode fingers of one comb electrode is greater than the distance from the upper surface of the first layer to the lower surface of the second layer.
[0014] The present invention is a filter including the above-described acoustic wave device.
[0015] The present invention is a multiplexer comprising the filter described above. Effect of the Invention
[0016] According to the present invention, it is possible to reduce the difference between the frequency temperature coefficient of the resonant frequency and the frequency temperature coefficient of the anti-resonant frequency. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1(a) is a plan view of an acoustic wave device in accordance with a first embodiment, and FIG. 1(b) is a cross-sectional view taken along line AA of FIG. 1(a). [Diagram 2] 2A to 2C are cross-sectional views illustrating a method for manufacturing the acoustic wave device in accordance with the first embodiment. [Diagram 3] FIG. 3 is a cross-sectional view of an acoustic wave device according to a comparative example. [Figure 4] 4(a) and 4(b) are diagrams showing simulation results of the frequency temperature coefficient in the comparative example. [Diagram 5] 5(a) and 5(b) are diagrams showing simulation results of the temperature coefficient of frequency when a piezoelectric layer including an LN layer and an LT layer is used. [Figure 6] FIG. 6 shows the simulation results of ΔTCF versus the cut angle of the LT layer when the thicknesses of the LN layer and the LT layer are fixed. [Figure 7] 7(a) and 7(b) are diagrams showing simulation results of ΔTCF when the LT layer is a 20° or 80° Y-cut X-propagation lithium tantalate layer. [Figure 8] 8(a) and 8(b) are diagrams showing suitable ranges of the cut angle and thickness ratio of the LN layer. [Figure 9] 9A to 9D are cross-sectional views of acoustic wave devices according to modifications of the first embodiment. [Figure 10] FIG. 10A is a plan view of an acoustic wave device in accordance with a second embodiment, and FIG. 10B is a cross-sectional view taken along line AA of FIG. 10A. [Figure 11] FIG. 11 shows the simulation results of ΔTCF versus the cut angle of the LN layer when the thicknesses of the LT layer and the LN layer are fixed. [Figure 12] 12(a) and 12(b) are diagrams showing simulation results of ΔTCF when the LN layer is a 20° or 80° Y-cut X-propagation lithium niobate layer. [Figure 13] 13(a) and 13(b) are diagrams showing suitable ranges of the cut angle and thickness ratio of the LT layer. [Figure 14] FIG. 14 is a circuit diagram of a filter in accordance with the third embodiment. [Figure 15] FIG. 15 is a circuit diagram of a duplexer in accordance with the fourth embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, embodiments of the present invention will be described with reference to the drawings. EXAMPLES
[0019] Fig. 1(a) is a plan view of an acoustic wave device 100 in accordance with a first embodiment, and Fig. 1(b) is a cross-sectional view taken along line AA of Fig. 1(a). In Fig. 1(a), an interdigital transducer (IDT) 31 and a reflector 35 are hatched for clarity. The arrangement direction of the electrode fingers 33 is the X direction, the extension direction of the electrode fingers 33 is the Y direction, and the thickness direction of the substrate 10 is the Z direction.
[0020] As shown in FIG. 1(a) and FIG. 1(b), an acoustic wave device 100 according to a first embodiment includes a piezoelectric layer 20 on a substrate 10. The piezoelectric layer 20 includes a lithium niobate (LiNbO3) layer 21 and a lithium tantalate (LiTaO3) layer 22 provided between the substrate 10 and the lithium niobate layer 21. Hereinafter, the lithium niobate layer 21 is referred to as an LN layer 21, and the lithium tantalate layer 22 is referred to as an LT layer 22. The LN layer 21 and the LT layer 22 are directly bonded to each other, for example. In this case, an amorphous layer of about several nm may be formed between the LN layer 21 and the LT layer 22. The thickness of the LN layer 21 is T1, and the thickness of the LT layer 22 is T2. The distance from the upper surface of the LN layer 21 to the lower surface of the LT layer 22 is T3. In the first embodiment, since the LN layer 21 and the LT layer 22 are directly bonded to each other, T3 is approximately equal to T1+T2, and corresponds approximately to the thickness of the piezoelectric layer 20.
[0021] An acoustic wave resonator 30 is provided on the LN layer 21. The acoustic wave resonator 30 includes an IDT 31 and a reflector 35. The reflectors 35 are provided on both sides of the IDT 31 in the X direction. The IDT 31 and the reflector 35 are formed of a metal film 36 on the LN layer 21.
[0022] The IDT 31 includes a pair of comb electrodes 32. The comb electrodes 32 include a plurality of electrode fingers 33 and a bus bar 34 to which the plurality of electrode fingers 33 are connected. The pair of comb electrodes 32 are provided facing each other such that the electrode fingers 33 are substantially alternately arranged. The plurality of electrode fingers 33 excite surface acoustic waves (mainly SH waves) on the piezoelectric layer 20. The surface acoustic waves excited by the plurality of electrode fingers 33 propagate mainly in the X direction. The average pitch P of the electrode fingers 33 of one of the pair of comb electrodes 32 is approximately the wavelength λ of the surface acoustic wave. In other words, twice the average pitch D of the electrode fingers 33 of the pair of comb electrodes 32 is approximately the wavelength λ of the surface acoustic wave. The reflector 35 reflects the surface acoustic wave excited by the electrode fingers 33. A protective film or a temperature compensation film covering the IDT 31 and the reflector 35 may be provided on the upper surface of the piezoelectric layer 20. The comb electrodes 32 may have dummy electrode fingers.
[0023] The substrate 10 is, for example, a sapphire substrate, a spinel substrate, a silicon substrate, a quartz substrate, a quartz substrate, or an alumina substrate. The sapphire substrate is a single crystal Al2O3 substrate, the spinel substrate is a single crystal or polycrystalline MgAl2O4 substrate, and the silicon substrate is a single crystal Si substrate. The quartz substrate is a single crystal SiO2 substrate, the quartz substrate is a polycrystalline SiO2 substrate, and the alumina substrate is a polycrystalline Al2O3 substrate.
[0024] The LN layer 21 is a single crystal lithium niobate layer, for example a rotated Y-cut X-propagation lithium niobate layer, and the LT layer 22 is a single crystal lithium tantalate layer, for example a rotated Y-cut X-propagation lithium tantalate layer.
[0025] The metal film 36 is a film containing aluminum (Al), copper (Cu), or molybdenum (Mo) as a main component. An adhesive film such as a titanium (Ti) film or a chromium (Cr) film may be provided between the metal film 36 and the LN layer 21. The adhesive film is thinner than the metal film 36.
[0026] As described in the above Patent Document 2 (JP Patent Publication 2019-201345 A), the surface acoustic wave excited by the electrode finger 33 propagates within 2.0 λ from the upper surface of the piezoelectric layer 20, and in particular propagates concentratedly within 1.0 λ from the upper surface of the piezoelectric layer 20. Therefore, in order that the energy of the surface acoustic wave exists in both the LN layer 21 and the LT layer 22, the distance T3 between the upper surface of the LN layer 21 and the lower surface of the LT layer 22 is set to 1.0 λ or less. In other words, the distance T3 between the upper surface of the LN layer 21 and the lower surface of the LT layer 22 is set to 1.0 times or less the average pitch P of the electrode fingers 33 of one comb-shaped electrode 32. The average pitch P may be calculated by dividing the length of the IDT 31 in the X direction by the number of pairs of the electrode fingers 33 (1 / 2 the number of the electrode fingers 33). In the first embodiment, the LN layer 21 and the LT layer 22 are directly bonded to each other, so that the thickness of the piezoelectric layer 20 is 1.0 λ or less. If the piezoelectric layer 20 is too thin, elastic waves will not be excited, so the total thickness (T1+T2) of the LN layer 21 and the LT layer 22 is preferably 0.1 times (0.1λ) or more the average pitch P of the electrode fingers 33, and more preferably 0.2 times (0.2λ) or more.
[0027] [Manufacturing method] 2(a) to 2(c) are cross-sectional views showing a manufacturing method of the acoustic wave device 100 according to the first embodiment. As shown in FIG. 2(a), a substrate 10 having a flat upper surface is prepared. The arithmetic mean roughness Ra of the upper surface of the substrate 10 is, for example, 1 nm or less. The upper surface of the substrate 10 and the lower surface of the LT layer 22 are bonded at room temperature. The LT layer 22 at this time is a layer (substrate) thicker than the LT layer 22 in FIG. 1(a) and FIG. 1(b). The room temperature bonding is performed, for example, by the following method. First, the upper surface of the substrate 10 and the lower surface of the LT layer 22 are irradiated with an ion beam, neutral beam, or plasma of an inert gas. This activates the upper surface of the substrate 10 and the lower surface of the LT layer 22. After the upper surface of the substrate 10 and the lower surface of the LT layer 22 are activated, the upper surface of the substrate 10 and the lower surface of the LT layer 22 are bonded at room temperature. This directly bonds the substrate 10 and the LT layer 22. An amorphous layer formed by integrating an amorphous layer made of the material of the substrate 10 with an amorphous layer made of the material of the LT layer 22 may be provided between the substrate 10 and the LT layer 22. Then, the upper surface of the LT layer 22 is polished by, for example, a chemical mechanical polishing (CMP) method to thin the LT layer 22 to a desired thickness.
[0028] As shown in FIG. 2(b), the upper surface of the LT layer 22 and the lower surface of the LN layer 21 are bonded at room temperature. The LN layer 21 at this time is a layer (substrate) thicker than the LN layer 21 in FIG. 1(a) and FIG. 1(b). The room temperature bonding is performed by the same method as in FIG. 2(a). That is, the upper surface of the LT layer 22 and the lower surface of the LN layer 21 are activated by irradiating them with an ion beam, neutral beam, or plasma of an inert gas, and then the upper surface of the LT layer 22 and the lower surface of the LN layer 21 are bonded at room temperature. As a result, the LN layer 21 and the LT layer 22 are directly bonded. An amorphous layer in which an amorphous layer of the material of the LN layer 21 and an amorphous layer of the material of the LT layer 22 are integrated may be provided between the LN layer 21 and the LT layer 22. Thereafter, the upper surface of the LN layer 21 is polished by, for example, a CMP method to thin it, and the LN layer 21 is made to have a desired thickness. The piezoelectric layer 20 is formed from the LN layer 21 and the LT layer 22 .
[0029] 2(c), an acoustic wave resonator 30 made of a metal film 36 is formed on the piezoelectric layer 20 by, for example, photolithography and etching. In this way, the acoustic wave device 100 in accordance with the first embodiment is formed.
[0030] [Comparative Example] Fig. 3 is a cross-sectional view of an acoustic wave device 500 according to a comparative example. As shown in Fig. 3, in the acoustic wave device 500 according to the comparative example, the piezoelectric layer 120 is made of a single layer of a single crystal lithium niobate layer or a single crystal lithium tantalate layer. The other configurations are the same as those in the first embodiment, and therefore the description thereof will be omitted.
[0031] [simulation] In a comparative example, a simulation was performed on the frequency-temperature characteristics when the piezoelectric layer 120 was a lithium niobate layer and when it was a lithium tantalate layer. The simulation was performed using the finite element method. The simulation conditions were as follows. Elastic wave wavelength λ: 1.5 μm IDT31 and reflector 35: Aluminum film with a thickness of 0.1λ Piezoelectric layer 120: Rotated Y-cut X-propagation lithium niobate layer with thickness T4 of 0.6λ, or rotated Y-cut X-propagation lithium tantalate layer with thickness T4 of 0.6λ Substrate 10: Sapphire substrate with a thickness of 3λ Temperature conditions: 25℃, 85℃
[0032] 4(a) and 4(b) are diagrams showing simulation results of temperature coefficients of frequency (TCF) in a comparative example. In FIG. 4(a), the horizontal axis is the cut angle of the piezoelectric layer 120, and the vertical axis is the TCF. The TCF of the resonant frequency when the piezoelectric layer 120 is a lithium niobate layer is shown by a black circle, and the TCF of the anti-resonant frequency is shown by a black triangle. The TCF of the resonant frequency when the piezoelectric layer 120 is a lithium tantalate layer is shown by a white circle, and the TCF of the anti-resonant frequency is shown by a white triangle. In FIG. 4(b), the horizontal axis is the cut angle of the piezoelectric layer 120, and the vertical axis is the difference ΔTCF between the TCF of the anti-resonant frequency and the TCF of the resonant frequency (ΔTCF=anti-resonant frequency TCF−resonant frequency TCF). The case where the piezoelectric layer 120 is a lithium niobate layer is shown by a black circle, and the case where the piezoelectric layer 120 is a lithium tantalate layer is shown by a white circle. The TCF of the resonant frequency was calculated by dividing the amount of change in the resonant frequency when the temperature changed from 25° C. to 85° C. by the temperature change of 60° C. Similarly, the TCF of the antiresonant frequency was calculated by dividing the amount of change in the antiresonant frequency when the temperature changed from 25° C. to 85° C. by the temperature change of 60° C.
[0033] As shown in FIG. 4(a), the TCFs of the resonant frequency and the anti-resonant frequency were negative regardless of whether the piezoelectric layer 120 was a lithium niobate layer or a lithium tantalate layer. The absolute value of the TCF of the resonant frequency was larger when the piezoelectric layer 120 was a lithium niobate layer (black circle) than when it was a lithium tantalate layer (white circle). On the other hand, the absolute value of the TCF of the anti-resonant frequency was smaller when the piezoelectric layer 120 was a lithium niobate layer (black triangle) than when it was a lithium tantalate layer (white triangle). As shown in FIG. 4(b), ΔTCF was a positive value when the piezoelectric layer 120 was a lithium niobate layer (black circle), whereas it was a negative value when the piezoelectric layer 120 was a lithium tantalate layer (white circle).
[0034] 4(a) and 4(b) show that when a lithium niobate layer is used for the piezoelectric layer 120, the TCF is smaller at the resonant frequency than the anti-resonant frequency, whereas when a lithium tantalate layer is used, the TCF is smaller at the anti-resonant frequency than the resonant frequency. In other words, the magnitude relationship of the TCF between the resonant frequency and the anti-resonant frequency is opposite for the lithium niobate layer and the lithium tantalate layer. Therefore, it is considered that the absolute value of ΔTCF can be reduced by forming the piezoelectric layer 20 as a laminate of the LN layer 21 and the LT layer 22 as in Example 1.
[0035] Therefore, a simulation was performed on the frequency-temperature characteristics when the piezoelectric layer 20 was a laminate of the LN layer 21 and the LT layer 22, as in Example 1. The simulation was performed using the finite element method. The simulation conditions were as follows. Elastic wave wavelength λ: 1.5 μm IDT31 and reflector 35: Aluminum film with a thickness of 0.1λ LN layer 21: 20° Y-cut X-propagation lithium niobate layer with a thickness T1 of 0.07λ to 0.5λ LT layer 22: 40° Y-cut X-propagation lithium tantalate layer with thickness T2 of 0.1λ to 0.53λ Thickness of the piezoelectric layer 20 (T1+T2): 0.6λ Substrate 10: Sapphire substrate with a thickness of 3λ Temperature conditions: 25℃, 85℃
[0036] 5(a) and 5(b) are diagrams showing the results of simulating the frequency temperature coefficient when the piezoelectric layer 20 including the LN layer 21 and the LT layer 22 is used. Table 1 is a table showing the results of simulating the frequency temperature coefficient when the piezoelectric layer 20 including the LN layer 21 and the LT layer 22 is used. In FIG. 5(a), the horizontal axis is the ratio of the thickness of the LN layer 21 to the total thickness of the LN layer 21 and the LT layer 22, and the vertical axis is the TCF. The TCF of the resonance frequency is shown by a black circle, and the TCF of the anti-resonance frequency is shown by a white circle. In FIG. 5(b), the horizontal axis is the ratio of the thickness of the LN layer 21 to the total thickness of the LN layer 21 and the LT layer 22, and the vertical axis is the absolute value of ΔTCF. For comparison, in FIG. 5(a), FIG. 5(b), and Table 1, the cases where the ratio of the thickness of the LN layer 21 is 0% or 100% are also shown. [Table 1]
[0037] As shown in Figures 5(a) and 5(b) and Table 1, it can be seen that the absolute value of ΔTCF can be reduced by using a piezoelectric layer 20 having an LN layer 21 and an LT layer 22 and by adjusting the thickness ratio of the LN layer 21 to the LT layer 22 appropriately.
[0038] Since the lithium niobate layer and the lithium tantalate layer are anisotropic materials, it is considered that the TCF changes depending on the cut angle. Therefore, a simulation was performed on the frequency temperature characteristics by changing the thickness ratio of the LN layer 21 and the LT layer 22 and the cut angle. The simulation was performed using the finite element method. The simulation conditions are as follows. The cut angle is set in the range of 0° to 80° so that the electrode fingers 33 excite surface acoustic waves (mainly SH waves). Elastic wave wavelength λ: 1.5 μm IDT31 and reflector 35: Aluminum film with a thickness of 0.1λ LN layer 21: 0° to 80° Y-cut X-propagation lithium niobate layer with a thickness T1 of 0.1λ to 0.5λ LT layer 22: 0° to 80° Y-cut X-propagation lithium tantalate layer with thickness T2 of 0.1λ to 0.5λ Thickness of the piezoelectric layer 20 (T1+T2): 0.6λ Substrate 10: Sapphire substrate with a thickness of 3λ Temperature conditions: 25℃, 85℃
[0039] Fig. 6 is a diagram showing simulation results of ΔTCF versus cut angle of LT layer 22 when the thicknesses of LN layer 21 and LT layer 22 are fixed. In Fig. 6, the thickness of LN layer 21 is fixed at 16.7% of the total thickness of LN layer 21 and LT layer 22. The horizontal axis of Fig. 6 is the cut angle of LT layer 22, and the vertical axis is ΔTCF. In Fig. 6, black circles represent the results when the cut angle of LN layer 21 is 0°, white circles represent the results when it is 20°, black triangles represent the results when it is 60°, and white triangles represent the results when it is 80°.
[0040] As shown in FIG. 4(b), the ΔTCF is positive for the lithium niobate layer, and negative for the lithium tantalate layer. The ΔTCF of the lithium niobate layer is large when the cut angle is small, and approaches 0 as the cut angle increases. The ΔTCF of the lithium tantalate layer is small when the cut angle is small, and approaches 0 as the cut angle increases. Therefore, as shown in FIG. 6, regardless of whether the cut angle of the LN layer 21 is 0°, 20°, 60°, or 80°, the ΔTCF is small when the cut angle of the LT layer 22 is 20°, and increases as the cut angle of the LT layer 22 increases.
[0041] 7(a) shows the simulation results of ΔTCF when the LT layer 22 is a 20° Y-cut X-propagation lithium tantalate layer, and Fig. 7(b) shows the simulation results of ΔTCF when the LT layer 22 is an 80° Y-cut X-propagation lithium tantalate layer. In Fig. 7(a) and Fig. 7(b), the horizontal axis represents the cut angle of the LN layer 21, and the vertical axis represents the ratio of the thickness of the LN layer 21 to the total thickness of the LN layer 21 and the LT layer 22.
[0042] 7(a) and 7(b), it can be seen that in both cases where the LT layer 22 is a 20° Y-cut X-propagation lithium tantalate layer and where the LT layer 22 is an 80° Y-cut X-propagation lithium tantalate layer, ΔTCF changes in the same manner with respect to the cut angle and thickness ratio of the LN layer 21. Therefore, it is considered that, regardless of the cut angle of the LT layer 22, ΔTCF changes in the same manner with respect to the cut angle and thickness ratio of the LN layer 21. Therefore, it is considered that an appropriate range of the cut angle and thickness ratio of the LN layer 21 can be determined using the results when the LT layer 22 is a 20° Y-cut X-propagation lithium tantalate layer.
[0043] 8(a) and 8(b) are diagrams showing appropriate ranges of the cut angle and thickness ratio of the LN layer 21. Fig. 8(a) shows the range where the absolute value of ΔTCF is approximately 20 ppm / °C or less. Fig. 8(b) shows the range where the absolute value of ΔTCF is approximately 10 ppm / °C or less.
[0044] 8(a), in order to keep the absolute value of ΔTCF at approximately 20 ppm / ° C. or less, it is desirable to set the cut angle and thickness ratio of the LN layer 21 within the ranges shown in Table 2 below. Note that the minimum value of the thickness ratio of the LN layer 21 in the simulation is 16.7%, but Tables 2 and 3 show the range in which ΔTCF is estimated to improve when the thickness ratio is less than 16.7% based on the contour lines. [Table 2]
[0045] As shown in Figure 8(a) and Table 2, (1) When the cut angle of the LN layer 21 is 0° or more and less than 55°, the ratio of the thickness of the LN layer 21 is more than 0% and 36% or less. (2) When the cut angle of the LN layer 21 is 55° or more and less than 70°, the ratio of the thickness of the LN layer 21 is more than 5% and 54% or less. (3) When the cut angle of the LN layer 21 is 70° or more and 80° or less, the ratio of the thickness of the LN layer 21 is more than 10% and 85% or less.
[0046] As shown in FIG. 8(b), in order to keep the absolute value of ΔTCF at about 10 ppm / ° C. or less, it is desirable to set the cut angle and thickness ratio of the LN layer 21 within the ranges of Table 3 below. [Table 3]
[0047] As shown in Figure 8(b) and Table 3, (1) When the cut angle of the LN layer 21 is 0° or more and less than 30°, the ratio of the thickness of the LN layer 21 is more than 5% and less than 24% (2) When the cut angle of the LN layer 21 is 30° or more and less than 50°, the ratio of the thickness of the LN layer 21 is more than 10% and 27% or less. (3) When the cut angle of the LN layer 21 is 50° or more and less than 60°, the ratio of the thickness of the LN layer 21 is more than 10% and less than 30%. (4) When the cut angle of the LN layer 21 is 60° or more and less than 70°, the ratio of the thickness of the LN layer 21 is more than 15% and 34% or less. (5) When the cut angle of the LN layer 21 is 70° or more and 80° or less, the ratio of the thickness of the LN layer 21 is more than 15% and less than 50%
[0048] [Variations] 9(a) to 9(d) are cross-sectional views of an acoustic wave device according to a modification of the first embodiment. As shown in FIG. 9(a), an acoustic wave device 100a according to the first modification of the first embodiment has a bonding layer 40 between an LN layer 21 and an LT layer 22. The bonding layer 40 is, for example, polycrystalline or amorphous, and is an aluminum oxide layer, a silicon nitride layer, an aluminum nitride layer, or a silicon layer. The bonding layer 40 may be a laminate of these layers. The thickness T5 of the bonding layer 40 is, for example, 1 nm to 50 nm. The other configurations are the same as those of the first embodiment, and therefore description thereof will be omitted. In this manner, the LN layer 21 and the LT layer 22 may be bonded by the bonding layer 40.
[0049] As shown in FIG. 9(b), an acoustic wave device 100b according to the second modification of the first embodiment has a temperature compensation layer 41 between the substrate 10 and the piezoelectric layer 20. The temperature compensation layer 41 is, for example, single crystal, polycrystal, or amorphous, and is a silicon oxide layer that is undoped or doped with fluorine or the like, a glass layer, or a quartz crystal layer. The other configurations are the same as those of the first modification of the first embodiment, and therefore will not be described. From the viewpoint of temperature compensation, the thickness T6 of the temperature compensation layer 41 is preferably 0.2 times (0.2λ) or more the average pitch P of the electrode fingers 33. If the temperature compensation layer 41 is too thick, loss increases. Therefore, the thickness T6 of the temperature compensation layer 41 is preferably 1.0 times (λ) or less the average pitch P of the electrode fingers 33. As described above, the surface acoustic wave excited by the electrode fingers 33 propagates within 2.0λ from the upper surface of the piezoelectric layer 20. Therefore, in order for the temperature compensation layer 41 to perform its temperature compensation function, it is preferable that the distance (T1+T5+T2+T6) between the upper surface of the piezoelectric layer 20 and the lower surface of the temperature compensation layer 41 be less than 2.0 times (2.0λ) the average pitch P of the electrode fingers 33.
[0050] As shown in FIG. 9(c), an acoustic wave device 100c according to the third modification of the first embodiment has a bonding layer 42 provided between the temperature compensating layer 41 and the piezoelectric layer 20. The bonding layer 42 is, for example, polycrystalline or amorphous, and is an aluminum oxide layer, a silicon nitride layer, an aluminum nitride layer, or a silicon layer. The bonding layer 42 may be a laminate of these layers. The thickness T7 of the bonding layer 42 is, for example, 1 nm to 50 nm. The other configurations are the same as those of the second modification of the first embodiment, and therefore description thereof will be omitted. In this manner, the temperature compensating layer 41 and the piezoelectric layer 20 may be bonded to each other by the bonding layer 42.
[0051] 9(d), in an acoustic wave device 100d according to the fourth modification of the first embodiment, the upper surface of the substrate 10 has a large surface roughness, and an intermediate layer 43 made of an insulating layer is provided between the substrate 10 and the temperature compensation layer 41. The intermediate layer 43 is, for example, an amorphous aluminum oxide layer. The thickness T8 of the intermediate layer 43 is, for example, 1.0 times (λ) or more the average pitch P of the electrode fingers 33. The other configurations are the same as those of the third modification of the first embodiment, and therefore description thereof will be omitted.
[0052] As described above, according to the first embodiment and its modification, the piezoelectric layer 20 provided on the substrate 10 includes the LN layer 21 and the LT layer 22 provided between the substrate 10 and the LN layer 21. The distance T3 from the upper surface of the LN layer 21 to the lower surface of the LT layer 22 is 1.0λ or less, and the surface acoustic wave excited by the electrode finger 33 propagates through both the LN layer 21 and the LT layer 22. As shown in FIG. 4(b), the ΔTCF is a positive value in the lithium niobate layer, whereas the ΔTCF is a negative value in the lithium tantalate layer. Therefore, by using the piezoelectric layer 20 including the LN layer 21 and the LT layer 22, the ΔTCF can be made close to 0, and the TCFs of both the resonant frequency and the antiresonant frequency can be improved.
[0053] Moreover, from the viewpoint of increasing the electromechanical coupling coefficient k2, the cut angle of the rotated Y-cut X-propagation lithium tantalate layer is preferably 50° or less, and more preferably 40° or less. As shown in FIG. 4(b), the absolute value of ΔTCF when a 40° Y-cut X-propagation lithium tantalate layer is used is greater than 20 ppm / °C, so in Example 1, it is preferable that ΔTCF is approximately 20 ppm / °C or less. Therefore, as shown in FIG. 8(a) and Table 2, when the total thickness of the LN layer 21 and the LT layer 22 is 100%, (1) When the cut angle of the LN layer 21 is equal to or greater than 0° and less than 55°, the ratio of the thickness of the LN layer 21 is preferably greater than 0% and equal to or less than 36%. (2) When the cut angle of the LN layer 21 is 55° or more and less than 70°, the ratio of the thickness of the LN layer 21 is preferably greater than 5% and less than 54%. (3) When the cut angle of the LN layer 21 is 70° or more and 80° or less, the ratio of the thickness of the LN layer 21 is preferably more than 10% and 85% or less.
[0054] From the viewpoint of reducing the absolute value of ΔTCF, (1) When the cut angle of the LN layer 21 is 0° or more and less than 55°, the proportion of the thickness of the LN layer 21 is preferably greater than 0% and less than 35%, more preferably greater than 0% and less than 34%, and even more preferably greater than 0% and less than 33%. (2) When the cut angle of the LN layer 21 is 55° or more and less than 70°, the thickness ratio of the LN layer 21 is preferably greater than 7% and less than 52%, more preferably greater than 9% and less than 50%, and further preferably greater than 11.5% and less than 47.5%. (3) When the cut angle of the LN layer 21 is 70° or more and 80° or less, the thickness ratio of the LN layer 21 is preferably greater than 10% and less than 83%, more preferably greater than 13% and less than 80%, and further preferably greater than 16% and less than 77%.
[0055] Also, as shown in FIG. 4(b), the absolute value of ΔTCF is greater than 10 ppm / °C when a 50° Y-cut X-propagation lithium tantalate layer is used. From this point of view, it is more preferable that ΔTCF is approximately 10 ppm / °C or less in Example 1. Therefore, as shown in FIG. 8(b) and Table 3, when the total thickness of the LN layer 21 and the LT layer 22 is 100%, (1) When the cut angle of the LN layer 21 is equal to or greater than 0° and less than 30°, the ratio of the thickness of the LN layer 21 is preferably greater than 5% and equal to or less than 24%. (2) When the cut angle of the LN layer 21 is 30° or more and less than 50°, the ratio of the thickness of the LN layer 21 is preferably greater than 10% and less than 27%. (3) When the cut angle of the LN layer 21 is 50° or more and less than 60°, the ratio of the thickness of the LN layer 21 is preferably more than 10% and not more than 30%. (4) When the cut angle of the LN layer 21 is equal to or greater than 60° and less than 70°, the ratio of the thickness of the LN layer 21 is preferably greater than 15% and equal to or less than 34%. (5) When the cut angle of the LN layer 21 is 70° or more and 80° or less, the ratio of the thickness of the LN layer 21 is preferably greater than 15% and less than 50%.
[0056] From the viewpoint of reducing the absolute value of ΔTCF, (1) When the cut angle of the LN layer 21 is 0° or more and less than 30°, the ratio of the thickness of the LN layer 21 is preferably greater than 5% and less than 23%, more preferably greater than 5% and less than 22.5%, and even more preferably greater than 5% and less than 22%. (2) When the cut angle of the LN layer 21 is 30° or more and less than 50°, the proportion of the thickness of the LN layer 21 is preferably greater than 10% and less than 26%, more preferably greater than 10% and less than 25%, and even more preferably greater than 10% and less than 24%. (3) When the cut angle of the LN layer 21 is 50° or more and less than 60°, the proportion of the thickness of the LN layer 21 is preferably greater than 10% and less than 29%, more preferably greater than 10% and less than 28%, and even more preferably greater than 10% and less than 27%. (4) When the cut angle of the LN layer 21 is 60° or more and less than 70°, the ratio of the thickness of the LN layer 21 is preferably greater than 15% and less than 31%, more preferably greater than 18% and less than 29%, and even more preferably greater than 20% and less than 27.5%. (5) When the cut angle of the LN layer 21 is 70° or more and 80° or less, the proportion of the thickness of the LN layer 21 is preferably greater than 15% and less than 45%, more preferably greater than 17.5% and less than 42.5%, and even more preferably greater than 20% and less than 41.5%.
[0057] From the viewpoint of increasing the electromechanical coupling coefficient k2, the cut angle of the rotated Y-cut X-propagation lithium niobate layer is preferably 50° or less, and more preferably 40° or less.
[0058] In addition, in Example 1, the LN layer 21 and the LT layer 22 of the piezoelectric layer 20 are directly bonded to each other. This makes it easier for the surface acoustic wave excited by the electrode fingers 33 to propagate through both the LN layer 21 and the LT layer 22. Therefore, by using the piezoelectric layer 20 including the LN layer 21 and the LT layer 22, it becomes easier to bring ΔTCF closer to 0. EXAMPLES
[0059] FIG. 10(a) is a plan view of an acoustic wave device 200 according to a second embodiment, and FIG. 10(b) is a cross-sectional view taken along line AA of FIG. 10(a). As shown in FIG. 10(a) and FIG. 10(b), the acoustic wave device 200 according to the second embodiment has a piezoelectric layer 20a provided on a substrate 10. The piezoelectric layer 20a includes a LT layer 22a and an LN layer 21a provided between the substrate 10 and the LT layer 22a. The LT layer 22a and the LN layer 21a are directly bonded to each other, for example. In this case, an amorphous layer of about several nm may be formed between the LT layer 22a and the LN layer 21a. The other configurations are the same as those of the first embodiment, and therefore will not be described.
[0060] The acoustic wave device 200 in accordance with the second embodiment can be manufactured in a manner similar to that for the acoustic wave device 100 in accordance with the first embodiment.
[0061] [simulation] A simulation of the frequency temperature characteristics was performed by changing the thickness ratio of the LT layer 22a and the LN layer 21a and the cut angle. The simulation was performed using the finite element method. The simulation conditions were as follows. Elastic wave wavelength λ: 1.5 μm IDT31 and reflector 35: Aluminum film with a thickness of 0.1λ LT layer 22a: 0° to 80° Y-cut X-propagation lithium tantalate layer having a thickness T1 of 0.1λ to 0.5λ LN layer 21a: 0° to 80° Y-cut X-propagation lithium niobate layer having a thickness T2 of 0.1λ to 0.5λ Thickness of the piezoelectric layer 20a (T1+T2): 0.6λ Substrate 10: Sapphire substrate with a thickness of 3λ Temperature conditions: 25℃, 85℃
[0062] Fig. 11 is a diagram showing the simulation results of ΔTCF versus the cut angle of the LN layer 21a when the thicknesses of the LT layer 22a and the LN layer 21a are fixed. In Fig. 11, the thickness of the LT layer 22a is fixed to be 16.7% of the total thickness of the LN layer 21a and the LT layer 22a. The horizontal axis of Fig. 11 is the cut angle of the LN layer 21a, and the vertical axis is ΔTCF. In Fig. 11, the black circles represent the results when the cut angle of the LT layer 22a is 0°, the white circles represent the results when it is 20°, and the white triangles represent the results when it is 80°.
[0063] 11, ΔTCF hardly changed even when the cut angle of the LN layer 21a was changed, regardless of whether the cut angle of the LT layer 22a was 0°, 20°, or 80°. This is presumably because the sound velocity of lithium niobate is slightly faster than that of lithium tantalate, and therefore the displacement of the surface acoustic wave tends to concentrate on the LT layer 22a side.
[0064] Fig. 12(a) shows the simulation results of ΔTCF when the LN layer 21a is a 20° Y-cut X-propagation lithium niobate layer, and Fig. 12(b) shows the simulation results of ΔTCF when the LN layer 21a is an 80° Y-cut X-propagation lithium niobate layer. In Fig. 12(a) and Fig. 12(b), the horizontal axis is the cut angle of the LT layer 22a, and the vertical axis is the ratio of the thickness of the LT layer 22a to the total thickness of the LT layer 22a and the LN layer 21a.
[0065] In the rotated Y-cut X-propagation lithium tantalate layer, the cut angle is preferably 50° or less in order to increase the electromechanical coupling coefficient k2. As shown in FIG. 12(a) and FIG. 12(b), when the cut angle of the LT layer 22a is 50° or less, when the LN layer 21a is a 20° Y-cut X-propagation lithium niobate layer, and when the LN layer 21a is an 80° Y-cut X-propagation lithium niobate layer, it can be seen that ΔTCF changes almost similarly with respect to the cut angle and thickness ratio of the LT layer 22a. It can also be seen that when the LN layer 21a is a 20° Y-cut X-propagation lithium niobate layer, the range in which ΔTCF is greater than 0 is slightly larger than when the LN layer 21a is an 80° Y-cut X-propagation lithium niobate layer. Therefore, it is considered that the appropriate range of the cut angle and thickness ratio of the LT layer 22a can be determined using the results when the LN layer 21a is a 20° Y-cut X-propagation lithium niobate layer.
[0066] 13(a) and 13(b) are diagrams showing appropriate ranges of the cut angle and thickness ratio of the LT layer 22a. Fig. 13(a) shows the range where the absolute value of ΔTCF is approximately 20 ppm / °C or less. Fig. 13(b) shows the range where the absolute value of ΔTCF is approximately 10 ppm / °C or less.
[0067] When the cut angle of the LT layer 22a is set to 50° or less so as to increase the electromechanical coupling coefficient k2, it is desirable to set the cut angle and thickness ratio of the LT layer 22a within the ranges of Table 4 below in order to keep the absolute value of ΔTCF at approximately 20 ppm / °C or less, as shown in FIG. 13(a). [Table 4] As shown in Figure 13(a) and Table 4, (1) When the cut angle of the LT layer 22a is 0° or more and less than 22.5°, the ratio of the thickness of the LT layer 22a is 10% or more and 40% or less. (2) When the cut angle of the LT layer 22a is 22.5° or more and less than 37.5°, the ratio of the thickness of the LT layer 22a is 10% or more and 51% or less. (3) When the cut angle of the LT layer 22a is 37.5° or more and 50° or less, the ratio of the thickness of the LT layer 22a is 13% or more and 85% or less.
[0068] As shown in FIG. 13(b), in order to keep the absolute value of ΔTCF at about 10 ppm / ° C. or less, it is desirable to set the cut angle and thickness ratio of the LT layer 22a within the ranges of Table 5 below. [Table 5] As shown in Figure 13(b) and Table 5, (1) When the cut angle of the LT layer 22a is 0° or more and less than 10°, the ratio of the thickness of the LT layer 22a is 12% or more and 20.5% or less. (2) When the cut angle of the LT layer 22a is 10° or more and less than 22.5°, the ratio of the thickness of the LT layer 22a is 12% or more and 26% or less. (3) When the cut angle of the LT layer 22a is 22.5° or more and less than 27.5°, the ratio of the thickness of the LT layer 22a is 12% or more and 34% or less. (4) When the cut angle of the LT layer 22a is 27.5° or more and less than 35°, the ratio of the thickness of the LT layer 22a is 12% or more and 41% or less. (5) When the cut angle of the LT layer 22a is 35° or more and less than 45°, the ratio of the thickness of the LT layer 22a is 21% or more and 46% or less. (6) When the cut angle of the LT layer 22a is 45° or more and 50° or less, the ratio of the thickness of the LT layer 22a is 25.5% or more and 50% or less.
[0069] As described above, according to the second embodiment, the piezoelectric layer 20a provided on the substrate 10 includes the LT layer 22a and the LN layer 21a provided between the substrate 10 and the LT layer 22a. The distance T3 from the upper surface of the LT layer 22a to the lower surface of the LN layer 21a is 1.0λ or less, and the surface acoustic wave excited by the electrode fingers 33 propagates through both the LT layer 22a and the LN layer 21a. Therefore, as in the first embodiment, ΔTCF can be brought close to 0, and the TCFs of both the resonant frequency and the antiresonant frequency can be improved.
[0070] From the viewpoint of increasing the electromechanical coupling coefficient k2, it is preferable that the LT layer 22a is a rotated Y-cut X-propagation lithium tantalate layer with a cut angle of 50° or less. In this case, as shown in FIG. 13(a) and Table 4, in order to reduce the absolute value of ΔTCF, when the total thickness of the LN layer 21a and the LT layer 22a is taken as 100%, (1) When the cut angle of the LT layer 22a is equal to or greater than 0° and less than 22.5°, the ratio of the thickness of the LT layer 22a is preferably equal to or greater than 10% and equal to or less than 40%. (2) When the cut angle of the LT layer 22a is 22.5° or more and less than 37.5°, the ratio of the thickness of the LT layer 22a is preferably 10% or more and 51% or less. (3) When the cut angle of the LT layer 22a is 37.5° or more and 50° or less, the ratio of the thickness of the LT layer 22a is preferably 13% or more and 85% or less.
[0071] From the viewpoint of reducing the absolute value of ΔTCF, (1) When the cut angle of the LT layer 22a is equal to or greater than 0° and less than 22.5°, the proportion of the thickness of the LT layer 22a is preferably equal to or greater than 10% and equal to or less than 38%, more preferably equal to or greater than 10% and equal to or less than 36%, and even more preferably equal to or greater than 10% and equal to or less than 35%. (2) When the cut angle of the LT layer 22a is 22.5° or more and less than 37.5°, the proportion of the thickness of the LT layer 22a is preferably 10% or more and 48% or less, more preferably 10% or more and 46% or less, and even more preferably 10% or more and 44% or less. (3) When the cut angle of the LT layer 22a is 37.5° or more and 50° or less, the thickness ratio of the LT layer 22a is preferably 14% or more and 85% or less, more preferably 16% or more and 85% or less, and even more preferably 17.5% or more and 85% or less.
[0072] In addition, as shown in FIG. 4(b), the absolute value of ΔTCF is larger than 10 ppm / ° C. when a 50° Y-cut X-propagation lithium tantalate layer is used. Therefore, in order to make the absolute value of ΔTCF approximately 10 ppm / ° C. or less, as shown in FIG. 13(b) and Table 5, when the total thickness of the LN layer 21a and the LT layer 22a is 100%, (1) When the cut angle of the LT layer 22a is equal to or greater than 0° and less than 10°, the ratio of the thickness of the LT layer 22a is preferably equal to or greater than 12% and equal to or less than 20.5%. (2) When the cut angle of the LT layer 22a is 10° or more and less than 22.5°, the ratio of the thickness of the LT layer 22a is preferably 12% or more and 26% or less. (3) When the cut angle of the LT layer 22a is 22.5° or more and less than 27.5°, the ratio of the thickness of the LT layer 22a is preferably 12% or more and 34% or less. (4) When the cut angle of the LT layer 22a is 27.5° or more and less than 35°, the ratio of the thickness of the LT layer 22a is preferably 12% or more and 41% or less. (5) When the cut angle of the LT layer 22a is 35° or more and less than 45°, the ratio of the thickness of the LT layer 22a is preferably 21% or more and 46% or less. (6) When the cut angle of the LT layer 22a is 45° or more and 50° or less, the ratio of the thickness of the LT layer 22a is preferably 25.5% or more and 50% or less.
[0073] From the viewpoint of reducing the absolute value of ΔTCF, (1) When the cut angle of the LT layer 22a is equal to or greater than 0° and less than 10°, the ratio of the thickness of the LT layer 22a is preferably equal to or greater than 12.5% and equal to or less than 19.5%, more preferably equal to or greater than 12.5% and equal to or less than 18.5%, and even more preferably equal to or greater than 12.5% and equal to or less than 17.5%. (2) When the cut angle of the LT layer 22a is 10° or more and less than 22.5°, the proportion of the thickness of the LT layer 22a is preferably 12.5% or more and 24% or less, more preferably 12.5% or more and 22% or less, and even more preferably 12.5% or more and 21% or less. (3) When the cut angle of the LT layer 22a is 22.5° or more and less than 27.5°, the ratio of the thickness of the LT layer 22a is preferably 12% or more and 32% or less, more preferably 12% or more and 30% or less, and even more preferably 12.5% or more and 28% or less. (4) When the cut angle of the LT layer 22a is 27.5° or more and less than 35°, the ratio of the thickness of the LT layer 22a is preferably 13% or more and 39% or less, more preferably 15% or more and 37.5% or less, and even more preferably 16% or more and 36% or less. (5) When the cut angle of the LT layer 22a is 35° or more and less than 45°, the ratio of the thickness of the LT layer 22a is preferably 22% or more and 44% or less, more preferably 24% or more and 42.5% or less, and even more preferably 25.5% or more and 41.5% or less. (6) When the cut angle of the LT layer 22a is 0.45° or more and 50° or less, the thickness ratio of the LT layer 22a is preferably 26.5% or more and 49% or less, more preferably 27.5% or more and 47% or less, and even more preferably 28.5% or more and 45% or less.
[0074] In the second embodiment, the configurations of the first to fourth modifications of the first embodiment may also be used.
[0075] In the first embodiment and its modified example, the piezoelectric layer 20 includes the LN layer 21 and the LT layer 22 provided between the substrate 10 and the LN layer 21. In the second embodiment, the piezoelectric layer 20a includes the LT layer 22a and the LN layer 21a provided between the substrate 10 and the LT layer 22a. However, the present invention is not limited to these cases. When using a piezoelectric layer including a first layer and a second layer provided between the substrate and the first layer, it is sufficient that the TCF of the resonant frequency in one of the first layer and the second layer is larger than the TCF of the resonant frequency in the other layer and the TCF of the anti-resonant frequency in one layer is smaller than the TCF of the anti-resonant frequency in the other layer when comb-shaped electrodes are provided on each of the first layer and the second layer. EXAMPLES
[0076] FIG. 14 is a circuit diagram of a filter according to a third embodiment. As shown in FIG. 14, in a filter 300 according to the third embodiment, one or more series resonators S1 to S4 are connected in series between an input terminal Tin and an output terminal Tout. One or more parallel resonators P1 to P3 are connected in parallel between the input terminal Tin and the output terminal Tout. The acoustic wave device according to the first embodiment, the modified example of the first embodiment, and the second embodiment can be used for at least one of the series resonators S1 to S4 and the parallel resonators P1 to P3. The numbers of the series resonators and the parallel resonators can be appropriately set. Although a ladder-type filter is shown as an example of the filter, other types such as a multimode filter may also be used. EXAMPLES
[0077] FIG. 15 is a circuit diagram of a duplexer according to a fourth embodiment. As shown in FIG. 15, in the duplexer 400 according to the fourth embodiment, a transmission filter 52 is connected between a common terminal Ant and a transmission terminal Tx, and a reception filter 54 is connected between the common terminal Ant and a reception terminal Rx. The transmission filter 52 passes a signal in a transmission band among high-frequency signals inputted from the transmission terminal Tx to the common terminal Ant as a transmission signal, and suppresses signals of other frequencies. The reception filter 54 passes a signal in a reception band among high-frequency signals inputted from the common terminal Ant to the reception terminal Rx as a reception signal, and suppresses signals of other frequencies. At least one of the transmission filter 52 and the reception filter 54 can be the filter 300 according to the third embodiment. Although a duplexer has been shown as an example of a multiplexer, a triplexer or a quadplexer may be used.
[0078] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to such specific embodiment, and various modifications and variations are possible within the scope of the gist of the present invention described in the claims. [Explanation of symbols]
[0079] 10...substrate, 20, 20a, 120...piezoelectric layer, 21, 21a...lithium niobate layer, 22, 22a...lithium tantalate layer, 30...acoustic wave resonator, 31...IDT, 32...comb-shaped electrode, 33...electrode finger, 34...bus bar, 35...reflector, 36...metal film, 40...bonding layer, 41...temperature compensation layer, 42...bonding layer, 43...intermediate layer, 52...transmitting filter, 54...receiving filter, 100, 100a, 100b, 100c, 100d, 200, 500...acoustic wave device, 300...filter, 400...duplexer
Claims
1. A substrate; a piezoelectric layer provided on the substrate, the piezoelectric layer having a lithium niobate layer and a lithium tantalate layer provided between the substrate and the lithium niobate layer; an elastic wave device comprising: a pair of comb electrodes provided on the lithium niobate layer, each of the comb electrodes having a plurality of electrode fingers that excite elastic waves, the average pitch of the plurality of electrode fingers of one of the comb electrodes being equal to or greater than the distance from the upper surface of the lithium niobate layer to the lower surface of the lithium tantalate layer.
2. the lithium niobate layer is a rotated Y-cut X-propagation lithium niobate layer; the lithium tantalate layer is a rotated Y-cut X-propagation lithium tantalate layer; When the total thickness of the lithium niobate layer and the lithium tantalate layer is taken as 100%, When the cut angle of the lithium niobate layer is 0° or more and less than 55°, the thickness ratio of the lithium niobate layer is greater than 0% and less than 36%, and When the cut angle of the lithium niobate layer is 55° or more and less than 70°, the thickness ratio of the lithium niobate layer is more than 5% and 54% or less, and 2. The acoustic wave device according to claim 1, wherein when the cut angle of the lithium niobate layer is 70° or more and 80° or less, the thickness ratio of the lithium niobate layer is more than 10% and 85% or less.
3. the lithium niobate layer is a rotated Y-cut X-propagation lithium niobate layer; the lithium tantalate layer is a rotated Y-cut X-propagation lithium tantalate layer with a cut angle of 50° or less; When the total thickness of the lithium niobate layer and the lithium tantalate layer is taken as 100%, When the cut angle of the lithium niobate layer is 0° or more and less than 30°, the ratio of the thickness of the lithium niobate layer is more than 5% and 24% or less, and When the cut angle of the lithium niobate layer is 30° or more and less than 50°, the ratio of the thickness of the lithium niobate layer is more than 10% and 27% or less, and When the cut angle of the lithium niobate layer is 50° or more and less than 60°, the ratio of the thickness of the lithium niobate layer is more than 10% and 30% or less, and When the cut angle of the lithium niobate layer is 60° or more and less than 70°, the ratio of the thickness of the lithium niobate layer is more than 15% and 34% or less, and 2. The acoustic wave device according to claim 1, wherein when the cut angle of the lithium niobate layer is 70 degrees or more and 80 degrees or less, the thickness ratio of the lithium niobate layer is more than 15% and 50% or less.
4. A substrate; a piezoelectric layer provided on the substrate, the piezoelectric layer having a lithium tantalate layer and a lithium niobate layer provided between the substrate and the lithium tantalate layer, the lithium tantalate layer and the lithium niobate layer each having a thickness ratio of 10% or more when the total thickness of the lithium tantalate layer and the lithium niobate layer is taken as 100%; an elastic wave device comprising: a pair of comb electrodes provided on the lithium tantalate layer, each of the comb electrodes having a plurality of electrode fingers for exciting an elastic wave, the average pitch of the plurality of electrode fingers of one of the comb electrodes being equal to or greater than the distance from the upper surface of the lithium tantalate layer to the lower surface of the lithium niobate layer.
5. the lithium tantalate layer is a rotated Y-cut X-propagation lithium tantalate layer with a cut angle of 50° or less; the lithium niobate layer is a rotated Y-cut X-propagation lithium niobate layer; When the total thickness of the lithium tantalate layer and the lithium niobate layer is taken as 100%, When the cut angle of the lithium tantalate layer is 0° or more and less than 22.5°, the thickness ratio of the lithium tantalate layer is 10% or more and 40% or less, and When the cut angle of the lithium tantalate layer is 22.5° or more and less than 37.5°, the thickness ratio of the lithium tantalate layer is 10% or more and 51% or less, and 5. The acoustic wave device according to claim 4, wherein when the cut angle of the lithium tantalate layer is 37.5 degrees or more and 50 degrees or less, the thickness ratio of the lithium tantalate layer is 13% or more and 85% or less.
6. the lithium tantalate layer is a rotated Y-cut X-propagation lithium tantalate layer with a cut angle of 50° or less; the lithium niobate layer is a rotated Y-cut X-propagation lithium niobate layer; When the total thickness of the lithium tantalate layer and the lithium niobate layer is taken as 100%, When the cut angle of the lithium tantalate layer is 0° or more and less than 10°, the thickness ratio of the lithium tantalate layer is 12% or more and 20.5% or less, and When the cut angle of the lithium tantalate layer is 10° or more and less than 22.5°, the thickness ratio of the lithium tantalate layer is 12% or more and 26% or less, and When the cut angle of the lithium tantalate layer is 22.5° or more and less than 27.5°, the thickness ratio of the lithium tantalate layer is 12% or more and 34% or less, and When the cut angle of the lithium tantalate layer is 27.5° or more and less than 35°, the thickness ratio of the lithium tantalate layer is 12% or more and 41% or less, and When the cut angle of the lithium tantalate layer is 35° or more and less than 45°, the thickness ratio of the lithium tantalate layer is 21% or more and 46% or less, and 5. The acoustic wave device according to claim 4, wherein when the cut angle of the lithium tantalate layer is 45 degrees or more and 50 degrees or less, the thickness ratio of the lithium tantalate layer is 25.5% or more and 50% or less.
7. The acoustic wave device according to claim 1 , wherein the lithium niobate layer and the lithium tantalate layer are directly bonded to each other.
8. A substrate; a piezoelectric layer comprising: a first layer provided on the substrate and made of a piezoelectric material; and a second layer provided between the substrate and the first layer and made of a piezoelectric material, wherein, when a pair of comb electrodes is provided on each of the first layer and the second layer, a frequency temperature coefficient of a resonant frequency in one of the first layer and the second layer is greater than a frequency temperature coefficient of a resonant frequency in the other layer and a frequency temperature coefficient of an anti-resonant frequency in the one layer is smaller than a frequency temperature coefficient of an anti-resonant frequency in the other layer, and when the total thickness of the first layer and the second layer is taken as 100%, the respective thicknesses of the first layer and the second layer are 10% or more; An acoustic wave device comprising: a pair of comb electrodes provided on the first layer, each having a plurality of electrode fingers that excite acoustic waves, wherein the average pitch of the plurality of electrode fingers of one comb electrode is equal to or greater than the distance from the top surface of the first layer to the bottom surface of the second layer.
9. A filter comprising the acoustic wave device of claim 1, 4 or 8.
10. A multiplexer comprising the filter of claim 9.
Citation Information
Patent Citations
Elastic wave device and module
JP2017034363A
Acoustic wave resonator, filter and multiplexer
JP2019201345A
Elastic wave resonator, filter, and multiplexer
JP2020123855A